The Role of Environmental Performance Moderation in the Effect of Green Innovation on Financial Performance - Pratiwi*, D.Ertin Eza; Effendy, Lukman (Universitas Syiah Kuala, 2023)
This research is a quantitative study that seeks to understand whether green innovation affects financial performance by moderating environmental performance. The subjects involved in this research include several manufacturing companies listed on the IDX during the 2019-2022 period. Meanwhile, the sample for this research was 30 companies taken. using the purposive sampling technique. Data processing and hypothesis testing using descriptive analysis, panel data regression estimation, traditional hypothesis testing, and moderated regression analysis (MRA). Use the Eviews 12 2023 application. The results of this research show that green innovation has a positive influence and significant impact on financial performance and the interaction between green innovation and environmental performance as a moderating variable has a positive and significant influence on financial performance. Environmental performance moderates the impact of environmentally friendly innovation on financial performance.